Previous Shoreline Dynamics Determine Future Susceptibility to Cyclone Impact in the Sundarban Mangrove Forest - Bhargava, Radhika; Friess, Daniel A. (Frontiers in Marine Science, 2022)
Extreme weather events are a cause of mangrove forest loss and degradation globally. Almost half of the world’s mangroves are found in the tropical cyclone belt, and forests often experience disturbance in structure, functioning and ecosystem service provision. Understanding the factors that increase the vulnerability of mangroves to such disturbances is a challenge. Using a novel remote sensing analysis combining water class change with vegetation classification, we showed that mangrove loss across multiple cyclone events is influenced by previous erosion history, suggesting that the prior state of the coastline affects susceptibility to future disturbance events. During Cyclone Amphan in May 2020, more than 1,200 km2 of mangroves were damaged and 40.6 km2 of shoreline was lost. Cyclone Amphan caused the most damage out of three recent cyclones, with the most mangrove loss (18.8%) experienced along shorelines that were eroding over the past 35 years. This can be explained by the long-term effect of erosion on the overall intertidal morphology of the shoreline. Landscape-scale mangrove management, particularly of sediment budgets is essential to switch previously eroding mangroves to a state where they can withstand cumulative storm impacts.